PENDIDIKAN KEIMANAN AHLUSSUNNAH WAL JAMA’AH PRESPEKTIF IMAM ABU HASAN AL ASY’ARI DALAM KITAB AL LUMA’ - Syariful Anam (Mentari : Journal of Islamic Primary School, 2023)
The education of the Ahlussunnah Wal Jama'ah faith, especially in our country, has become a very important ideology. This is because the Ahlussunnah faith is followed by almost half of the Muslim population in Indonesia. The Ahlussunnah Wal Jama'ah ideology that we follow is pioneered by two major parties, Imam Abu Hasan Al-Asy'ari and Imam Abu Mansur Al Maturidi. Nowadays, there are still many who do not know about the ideologies or sects that they follow, but instead, there are many who provoke or divide the unity of the Muslim community in Indonesia. This research is based on literature and data analysis using hermeneutic and content analysis methods. The results of this study are that the Ahlussunnah Wal Jama'ah creed can answer problems in the diversity of Islam, and Ahlussunnah Wal Jama'ah is the most appropriate ideology for faith education that is in accordance with nationalism.